Evaluation and validation of laboratory procedures for the surveillance of ESBL-, AmpC-, and carbapenemase-producing Escherichia coli from fresh meat and caecal samples - Hendriksen, Rene S.; Cavaco, Lina M.; Guerra, Beatriz; Bortolaia, Valeria; Agersø, Yvonne; Svendsen, Christina Aaby; Nielsen, Hanne Nørgaard; Kjeldgaard, Jette Sejer; Pedersen, Susanne Karlsmose; Fertner, Mette; Hasman, Henrik (Frontiers in Microbiology, 2023)
Extended-spectrum β-lactamase-(ESBL) and AmpC-β-lactamase-producing Enterobacterales are widely distributed and emerging in both human and animal reservoirs around the world. A growing concern has emerged in Europe following the appearance of also carbapenemaseproducing Escherichia coli (E. coli) in the primary production of food animals.In 2013, the European Commission (EC) issued the Implementing Decision on the monitorin g and reporting of antimicrobial resistance in zoonotic and commensal bacteria. The European Union Reference Laboratory for Antimicrobial Resistance (EURL-AR) was tasked to provide two laboratory protocols for samples derived from meat and caecal content, respectively for the isolation of ESBL-and AmpC producing E. coli (part 1) and carbapenemase-producing E. coli (part 2). Here, we describe the current protocols including the preparatory work for the development.Up to nine laboratory procedures were tested using minced meat as matrix from beef, pork and chicken as well as six procedures for caecal content of the cattle, pigs and chicken. Variables included sample volume, pre-enrichment volume, pre-enrichment broth with and without antimicrobial supplementation, and incubation time/temperature. The procedures were evaluated against up to nine E. coli strains harbouring different AMR genes belonging to the three β-lactamase groups.The laboratory procedures tested revealed that the most sensitive and specific methodologies were based on a Buffered Peptone Water pre-enrichment of 225 ml to 25g or 9 ml to 1g for minced meat and caecal content, respectively, incubated at 37ºC over-night followed by inoculation onto MacConkey agar supplemented with 1 mg/L cefotaxime for the detection of ESBL-and AmpC-producing E. coli and Chrom ID SMART (Chrom ID CARBA and OXA) for carbapenemase-producing E. coli and incubated over-night at 37ºC and 44ºC, respectively.